Syar’u Man Qablanâ and It’s Implementation in Sharia Economic Law (Mu’amalah Mâliyyah) - Panji Adam Agus Putra (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
The terms of the earlier people's sharia or called syar’u man qablanâ are one of the legal arguments in Islam that have been debated by scholars related to their validity. Therefore, it is necessary to conduct related research on the concept of syar’u man qablanâ and its implementation in the field of mu’âmalah mâliyyah. This research uses a normative juridical approach. The sources of this study are primary and secondary sources. This research is descriptive and classified as qualitative research. The results showed that the implementation of the sharia of the previous people in the field of mu’âmalah mâliyyah was the Ju’âlah contract, the Ijârah contract, the Dhamân Mâ Tafsadahu al-Dawwâb al-Mursalah, the kafâlah bi al-wajh (bi al-nafs) contract and the qismah muhaya’ah contract.